Penerapan Metode Grand MBA dalam Peningkatan Kemampuan Membaca Al-Qur’an Siswa Madrasah Tsanawiyah Al Burhan Semarang Tahun Ajaran 2022/2023 - Moh Jihadul Fath; Edy Muslimin; M. Yunan Hidayat (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
Application of the GRAND MBA Method in Improving the Reading Ability of Al-Qur'an Students at Madrasah Tsanawiyah Al Burhan. The background of this research is that there are still students who are not proficient in reading the Al-Qur'an and the students' lack of understanding of tajwid and makharijul letters of the Al-Qur'an. The purpose of this study was to find out 1) Application of the GRAND MBA Method in Improving Al-Qur'an Reading Ability of Madrasah Tsanawiyah Al Burhan Students, 2) Ability to read Al-Qur'an of students at Madrasah Tsanawiyah Al Burhan. This research is a qualitative research. The subjects were students and Al-Qur'an teachers while the informants were madrasah heads, Al-Qur'an teachers and Waka Curriculum. Data collection techniques carried out by researchers using interview techniques, observation and documentation. Test the validity of the data using triangulation while data analysis techniques through data reduction, data presentation and drawing conclusions. The results of this study indicate that 1) The application of the GRAND MBA method also reveals an increase in students' ability to read the Qur'an. This can be seen from the ability of students to pronounce Arabic letters well, apply the tajwid laws correctly, read the Qur'an more smoothly and can interpret the verses of the Qur'an in words. 2) The process of applying the GRAND MBA Method in increasing the ability to read the Koran from semester 1 to semester 2 and there was an increase of 87%.